Um parente na estante do museu : etnografia sobre Jorminhot, estátua sagrada dos índios Krenak - Walison Vasconcelos Pascoal (2019)
This thesis is an ethnography on Jorminhot, a sacred post/statue of the Krenak Indians (macro jê), which is under the custody of the Museu Paraense Emílio Goeldi, in Belém do Pará. This statue was "collected" by the ethnologist Curt Nimuendaju in 1939 at the Posto Indígena Guido Marlière, currently Terra Indígena Krenak, in east of Minas Gerais. The research that underlies this work was constructed collaboratively with some leaders of the Krenak People, in order to meet their desire to recognize Jorminhot. By describing and analysing this expedition of recognition to the Museu Goeldi, as well as of some aspects of the indigenous narratives, it becomes clear that the Museum and the Krenak construct divergent senses on the statue and its trajectory, like collection and theft, material and spiritual, object and relative, replica and original. It is suggested that more than a "contact zone" that calls into question different meanings about an “object”, the museum can be seen as a "zone of cosmopolitical contact" endowed with ritual efficacy. One of the aims of the Krenak is to obtain the restitution of the statue, so this ethnography seeks to provide elements for understanding the efficacy and meaning that the Krenak attribute to it.